hsa_circ_0001599 promotes odontogenic differentiation of human dental pulp stem cells by increasing ITGA2 expression and stability - Yeqing Yang; Chong Jiang; Junkai Zeng; Xiaolan Guo; Ming Chen; Buling Wu (Communications Biology)
Abstract Dental pulp regeneration is significantly aided by human dental pulp stem cells (hDPSCs). An increasing number of studies have demonstrated that circular RNAs (circRNAs) are crucial in the multidirectional differentiation of many mesenchymal stem cells, but their specific functions and mechanisms remain unknown. This work aimed at elucidating the molecular mechanism by which hsa_circ_0001599 works in hDPSCs during odontogenic differentiation. The expression of hsa_circ_0001599 in hDPSCs and dental pulp tissue was determined by using quantitative real-time PCR (qRT‒PCR). The role of hsa_circ_0001599 in the odontogenic differentiation of hDPSCs and its mechanism were studied using a variety of in vivo and in vitro assessments. The odontogenic differentiation of hDPSCs was facilitated by the overexpression of hsa_circ_0001599, which activated the PI3K/AKT signalling pathway in vitro. In vivo, hsa_circ_0001599 can promote the formation of new dentin-like structures. Mechanistically, hsa_circ_0001599 enhanced ITGA2 expression by sponging miR-889-3p. Furthermore, hsa_circ_0001599 interacts with the methylation reader hnRNPA2B1, promoting hnRNPA2B1 translocation from the nucleus to the cytoplasm and increasing ITGA2 mRNA stability. This research revealed the important role of hsa_circ_0001599 in odontogenic differentiation. Thus, hDPSCs engineered with hsa_circ_0001599 have the potential to be effective therapeutic targets for dental pulp repair and regeneration.